Fermentação alcoólica com levedura imobilizada em colmos de bambu e em fibra de coco - Santos, Adeilton Malafaia dos (2008)
This paper aims to compare qualitatively and quantitatively alcoholic fermentation promoted by yeast Saccharomyces cerevisiae cells immobilized in three inert supports: fiber of dwarf coconut (Cocos nucifera) and two varieties of bamboo (Phyllostachys caniço and Guadua angustifolia). The three materials were also evaluated on their use as supports. The process of immobilization was dumping of equal volumes of materials (two liters) into a suspension of yeast cells (in order of 109 cells / mL) followed by drainage and consequent food with equal volumes of must of molasses. The pH must was adjusted with commercial sulfuric acid to around 4.20 and received addition of 3 ppm of bactericidal for control of bacterial contamination. There was also addition of 10 ppm of nutrient for fermentation in all fermentative cycles. At the end of ninety-one fermentative cycles the process was interrupted, and observed that the three materials have proved physical resistance and that the efficiency of the process and efficiency of fermentation of yeast-coconut system had values above those of yeast-bamboo systems since initial stages, showing to be the fiber of coconut support for the immobilization of cells more efficient. However, around the cycle of number seventy-four, the three systems began to provide similar efficiencies, which suggests that there has been a gradual increase in the number of yeast cells immobilized in systems yeast-bamboo during the cycles. The counting of cells in free media fermented showed that there was satisfactory cell detachment related with the figures already cited in the literature.